2013
DOI: 10.1371/journal.pone.0070479
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Induction of Transforming Growth Factor-Beta1 in Rat Models Enhances Radiation Injury in the Intestine and the Heart

Abstract: Radiation therapy in the treatment of cancer is dose limited by radiation injury in normal tissues such as the intestine and the heart. To identify the mechanistic involvement of transforming growth factor-beta 1 (TGF-β1) in intestinal and cardiac radiation injury, we studied the influence of pharmacological induction of TGF-β1 with xaliproden (SR 57746A) in rat models of radiation enteropathy and radiation-induced heart disease (RIHD). Because it was uncertain to what extent TGF-β induction may enhance radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 57 publications
(56 reference statements)
0
35
0
Order By: Relevance
“…TGF-β is known to play a critical role in cardiac injury, repair and remodeling (25). Using a TGF-β agonist, Boerma et al recently reported on a direct effect of TGF-β on radiation-induced cardiac injury (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β is known to play a critical role in cardiac injury, repair and remodeling (25). Using a TGF-β agonist, Boerma et al recently reported on a direct effect of TGF-β on radiation-induced cardiac injury (26).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β is involved in the pathogenesis of several cardiac diseases, affecting both the inflammatory and reparative responses to injury (25). The timing and levels of TGF-β inhibition appear to be crucial for preventing inflammation and/or excessive collagen deposition leading to cardiac dysfunction (26). IPW-5371 preserved the response to β-adrenergic stimulation and reduced collagen deposition after irradiation; however, we observed a slight reduction in right ventricular function (RVFAC and TAPSE) associated with IPW-5371 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Total cardiac RNA was isolated, cDNA synthesized, and steady-state mRNA levels were measured with real-time quantitative PCR (TaqMan™) as described before [19] and in the Supplementary Material, using the pre-designed TaqMan Gene Expression Assays™ listed in Supplementary Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Strikingly, the predicted activation of the TGFβ1 regulatory pathway by RT appears to be significantly attenuated if HBOT is applied. The TGFβ-pathway is strongly associated with radiationinduced fibrosis in different organs, and is the subject of investigation regarding possible antifibrotic therapies (36)(37)(38)(39).…”
Section: Continued On Next Pagementioning
confidence: 99%
“…PDGF has been shown to influence the TGFβ-pathway and is implicated to be involved in fibrosis as well (63). The suppression of TGFβ and PDGF as potential antifibrotic therapies is of interest and has been investigated in several studies (37,41). Fibrosis is a complex process involving several pathways that are interconnected and the concurrent suppression of more of these factors is more likely to have an effect on a biological process.…”
Section: Continued On Next Pagementioning
confidence: 99%